Multiplexed immunofluorescence reveals potential PD-1/PD-L1 pathway vulnerabilities in craniopharyngioma. Issue 8 (2nd March 2018) - Coy, Shannon; Rashid, Rumana; Lin, Jia-Ren; Du, Ziming; Donson, Andrew M; Hankinson, Todd C; Foreman, Nicholas K; Manley, Peter E; Kieran, Mark W; Reardon, David A; Sorger, Peter K; Santagata, Sandro
Abstract: Background: Craniopharyngiomas are neoplasms of the sellar/parasellar region that are classified into adamantinomatous craniopharyngioma (ACP) and papillary craniopharyngioma (PCP) subtypes. Surgical resection of craniopharyngiomas is challenging, and recurrence is common, frequently leading to profound morbidity. BRAF V600E mutations render PCP susceptible to BRAF/MEK inhibitors, but effective targeted therapies are needed for ACP. We explored the feasibility of targeting the programmed cell death protein 1/programmed death-ligand 1 (PD-1/PD-L1) immune checkpoint pathway in ACP and PCP. Methods: We mapped and quantified PD-L1 and PD-1 expression in ACP and PCP resections using immunohistochemistry, immunofluorescence, and RNA in situ hybridization. We used tissue-based cyclic immunofluorescence to map the spatial distribution of immune cells and characterize cell cycle and signaling pathways in ACP tumor cells which intrinsically express PD-1. Results: All ACP (15 ± 14% of cells, n = 23, average ± SD) and PCP (35 ± 22% of cells, n = 18) resections expressed PD-L1. In ACP, PD-L1 was predominantly expressed by tumor cells comprising the cyst lining. In PCP, PD-L1 was highly expressed by tumor cells surrounding the stromal fibrovascular cores. ACP also exhibited tumor cell–intrinsic PD-1 expression in whorled epithelial cells with nuclear-localized beta-catenin. These cells exhibited evidence of elevated mammalian target of rapamycin (mTOR) and mitogen-activated protein kinase (MAPK) signaling. Profiling of immune populations in ACP and PCP showed a modest density of CD8+ T cells. Conclusions: ACP exhibit PD-L1 expression in the tumor cyst lining and intrinsic PD-1 expression in cells proposed to comprise an oncogenic stem-like population. In PCP, proliferative tumor cells express PD-L1 in a continuous band at the stromal–epithelial interface. Targeting PD-L1 and/or PD-1 in both subtypes of craniopharyngioma might therefore be an effective therapeutic strategy.